Is decoupling enough to achieve the U.S. climate targets for agriculture and forestry? Historical greenhouse gas and biomass fluxes from AFOLU sector production in the United States, 1910–2022 - Andreas Magerl; Karl-Heinz Erb; Christian Lauk; Nicolas Roux; Simone Gingrich (Ecological Economics, 2025)

Slow and unequal reduction in Austrian household GHG footprints between 2000 and 2020 - Christian Dorninger; Simone Gingrich; Willi Haas; Alina Brad; Etienne Schneider; Dominik Wiedenhofer (Journal of Industrial Ecology, 2025)
Understanding the trends and distribution of greenhouse gas (GHG) emissions embodied in household consumption is pivotal to developing climate‐change mitigation strategies that are just and effective. While household GHG footprints inequality is increasingly investigated, less is known about its temporal dynamics across product groups. For the case of Austria, we (1) develop a database for household GHG footprints from 2000 to 2020 by combining multi‐regional input–output modeling with household budget surveys, (2) investigate temporal trends across consumption categories and income groups, and (3) explore socio‐economic explanatory variables. We find that the sum of Austrian household GHG footprints declined from 73 Mt CO2eq in 2000 to 67 Mt CO2eq in 2020. In 2005, when Austrian GHG emissions peaked, the highest income decile induced 3.5 times more GHG emissions than the lowest income decile. This factor remained similarly high at 3.4 until 2020, particularly due to trends in the consumption categories mobility and goods . The most notable GHG reduction was achieved in housing/heating , where carbon inequality was less pronounced. Beyond income, floor space, car ownership, the heating system, household size, and the number of vacations significantly affect GHG footprints. Our findings suggest that reducing stubbornly high carbon inequality, particularly in the consumption of mobility and goods , can contribute to more effective climate‐change mitigation.

Correction to: Agroforestry trade-offs between biomass provision and aboveground carbon sequestration in the alpine Eisenwurzen region, Austria - Bastian Bertsch-Hoermann; Claudine Egger; Veronika Gaube; Simone Gingrich (Regional Environmental Change, 2025)

Linking forest carbon opportunity costs and greenhouse gas emission substitution effects of wooden buildings: The climate optimum concept - Dominik Maierhofer; Vincent van Karsbergen; Tajda Potrč Obrecht; Marcella Ruschi Mendes Saade; Simone Gingrich; Wolfgang Streicher; Karl-Heinz Erb; Alexander Passer (Sustainable Production and Consumption, 2024)

Analyzing long-term dynamics of agricultural greenhouse gas emissions in Austria, 1830–2018 - Christian Lauk; Andreas Magerl; Julia le Noë; Michaela C. Theurl; Simone Gingrich (Science of The Total Environment, 2024)

Beyond the Farm to Fork Strategy: Methodology for designing a European agro-ecological future - Gilles Billen; Eduardo Aguilera; Rasmus Einarsson; Josette Garnier; Simone Gingrich; Bruna Grizzetti; Luis Lassaletta; Julia Le Noë; Alberto Sanz-Cobena (Science of The Total Environment, 2024)

Mechanisms to exclude local people from forests: Shifting power relations in forest transitions - Melanie Pichler; Martin Schmid; Simone Gingrich (Ambio, 2022)
Forest transitions may significantly contribute to climate change mitigation but also change forest use, affecting the local people benefiting from forests. We analyze forest transitions as contested processes that simplify multifunctional landscapes and alter local livelihoods. Drawing on the Theory of Access, we develop a conceptual framework to investigate practices of multifunctional forest use and the mechanisms that exclude local forest use(r)s during forest transitions in nineteenth century Austria and twenty-first century Lao PDR. Based on historical sources, interviews and secondary literature, we discuss legal, structural and social-metabolic mechanisms to exclude multifunctional forest practices, marginalizing peasants and shifting cultivators. These include, for example, the increasing enforcement of private ownership in forests or the shift from fuelwood to coal in Austria and restrictive land use planning or the expansion of private land concessions in Laos. By integrating political ecology and environmental history in forest transitions research we unravel shifting power relations connected to forest change.

Land use intensification increasingly drives the spatiotemporal patterns of the global human appropriation of net primary production in the last century - Thomas Kastner; Sarah Matej; Matthew Forrest; Simone Gingrich; Helmut Haberl; Thomas Hickler; Fridolin Krausmann; Gitta Lasslop; Maria Niedertscheider; Christoph Plutzar; Florian Schwarzmüller; Jörg Steinkamp; et al. (Global Change Biology, 2022)
Land use has greatly transformed Earth's surface. While spatial reconstructions of how the extent of land cover and land‐use types have changed during the last century are available, much less information exists about changes in land‐use intensity. In particular, global reconstructions that consistently cover land‐use intensity across land‐use types and ecosystems are missing. We, therefore, lack understanding of how changes in land‐use intensity interfere with the natural processes in land systems. To address this research gap, we map land‐cover and land‐use intensity changes between 1910 and 2010 for 9 points in time. We rely on the indicator framework of human appropriation of net primary production (HANPP) to quantify and map land‐use‐induced alterations of the carbon flows in ecosystems. We find that, while at the global aggregate level HANPP growth slowed down during the century, the spatial dynamics of changes in HANPP were increasing, with the highest change rates observed in the most recent past. Across all biomes, the importance of changes in land‐use areas has declined, with the exception of the tropical biomes. In contrast, increases in land‐use intensity became the most important driver of HANPP across all biomes and settings. We conducted uncertainty analyses by modulating input data and assumptions, which indicate that the spatial patterns of land use and potential net primary production are the most critical factors, while spatial allocation rules and uncertainties in overall harvest values play a smaller role. Highlighting the increasing role of land‐use intensity compared to changes in the areal extent of land uses, our study supports calls for better integration of the intensity dimension into global analyses and models. On top of that, we provide important empirical input for further analyses of the sustainability of the global land system.

Agroforestry trade-offs between biomass provision and aboveground carbon sequestration in the alpine Eisenwurzen region, Austria - Bastian Bertsch-Hoermann; Claudine Egger; Veronika Gaube; Simone Gingrich (Regional Environmental Change, 2021)
Mountain agroecosystems deliver essential ecosystem services to society but are prone to climate change as well as socio-economic pressures, making multi-functional land systems increasingly central to sustainable mountain land use policy. Agroforestry, the combination of woody vegetation with crops and/or livestock, is expected to simultaneously increase provisioning and regulating ecosystem services, but knowledge gaps concerning trade-offs exist especially in temperate industrialized and alpine regions. Here, we quantify the aboveground carbon (C) dynamics of a hypothetical agroforestry implementation in the Austrian long-term socio-ecological research region Eisenwurzen from 2020 to 2050. We develop three land use scenarios to differentiate conventional agriculture from an immediate and a gradual agroforestry implementation, integrate data from three distinct models (Yield-SAFE, SECLAND, MIAMI), and advance the socio-ecological indicator framework Human Appropriation of Net Primary Production (HANPP) to assess trade-offs between biomass provision and carbon sequestration. Results indicate that agroforestry strongly decreases HANPP because of a reduction in biomass harvest by up to − 47% and a simultaneous increase in actual net primary production by up to 31%, with a large amount of carbon sequestered in perennial biomass by up to 3.4 t C ha -1 yr -1 . This shows that a hypothetical transition to agroforestry in the Eisenwurzen relieves the agroecosystem from human-induced pressure but results in significant trade-offs between biomass provision and carbon sequestration. We thus conclude that while harvest losses inhibit large-scale implementation in intensively used agricultural regions, agroforestry constitutes a valuable addition to sustainable land use policy, in particular when affecting extensive pastures and meadows in alpine landscapes.

The Sustainable Development Goals prioritize economic growth over sustainable resource use: a critical reflection on the SDGs from a socio-ecological perspective - Nina Eisenmenger; Melanie Pichler; Nora Krenmayr; Dominik Noll; Barbara Plank; Ekaterina Schalmann; Marie-Theres Wandl; Simone Gingrich (Sustainability Science, 2020)
The sustainable development goals (SDGs) were adopted in 2015, succeeding the Millennium Development Goals (MDGs). While the MDGs focused on improving well-being in the developing world, the 17 SDGs address all countries and aim at reconciling economic and social with ecological goals. We adopt a social ecology perspective and critically reflect on the SDGs’ potential for monitoring, supporting, and bringing about a transformation towards sustainability. Starting from a literature review on the SDGs, we link empirical findings from social ecology with analyses of SDG targets and indicators. First, we find that the SDGs fail to monitor absolute trends in resource use and thus prioritize economic growth over ecological integrity. Second, we discuss the contradictions between economic growth and sustainable resource use in early and late stages of industrialization processes and show that they are responsible for important trade-offs among SDG targets. Third, we analyze the transformative potential of the SDGs with a focus on the actors and institutions addressed to bring about transformative change. We find that the SDGs rely mainly on those institutions responsible for unsustainable resource use, and partly propose measures that even reinforce current trends towards less sustainability. Despite ascertaining limited transformative potential to the SDGs from an analytical perspective, we conclude by stressing the strategic relevance of the SDGs for visions, research, and practices of statt towards transformative change towards sustainability.

Modeling and empirical validation of long‐term carbon sequestration in forests (France, 1850–2015) - Julia Le Noë; Sarah Matej; Andreas Magerl; Manan Bhan; Karl‐Heinz Erb; Simone Gingrich (Global Change Biology, 2020)
The development of appropriate tools to quantify long‐term carbon (C) budgets following forest transitions, that is, shifts from deforestation to afforestation, and to identify their drivers are key issues for forging sustainable land‐based climate‐change mitigation strategies. Here, we develop a new modeling approach, CRAFT (CaRbon Accumulation in ForesTs) based on widely available input data to study the C dynamics in French forests at the regional scale from 1850 to 2015. The model is composed of two interconnected modules which integrate biomass stocks and flows (Module 1) with litter and soil organic C (Module 2) and build upon previously established coupled climate‐vegetation models. Our model allows to develop a comprehensive understanding of forest C dynamics by systematically depicting the integrated impact of environmental changes and land use. Model outputs were compared to empirical data of C stocks in forest biomass and soils, available for recent decades from inventories, and to a long‐term simulation using a bookkeeping model. The CRAFT model reliably simulates the C dynamics during France's forest transition and reproduces C‐fluxes and stocks reported in the forest and soil inventories, in contrast to a widely used bookkeeping model which strictly only depicts C‐fluxes due to wood extraction. Model results show that like in several other industrialized countries, a sharp increase in forest biomass and SOC stocks resulted from forest area expansion and, especially after 1960, from tree growth resulting in vegetation thickening (on average 7.8 Mt C/year over the whole period). The difference between the bookkeeping model, 0.3 Mt C/year in 1850 and 21 Mt C/year in 2015, can be attributed to environmental and land management changes. The CRAFT model opens new grounds for better quantifying long‐term forest C dynamics and investigating the relative effects of land use, land management, and environmental change.

Agroecosystem energy transitions: exploring the energy-land nexus in the course of industrialization - Simone Gingrich; Geoff Cunfer; Eduardo Aguilera (Regional Environmental Change, 2018)

Agroecosystem energy transitions in the old and new worlds: trajectories and determinants at the regional scale - Simone Gingrich; Inés Marco; Eduardo Aguilera; Roc Padró; Claudio Cattaneo; Geoff Cunfer; Gloria I. Guzmán; Joshua MacFadyen; Andrew Watson (Regional Environmental Change, 2018)

Regional specialization and market integration: agroecosystem energy transitions in Upper Austria - Simone Gingrich; Michaela Clarissa Theurl; Karlheinz Erb; Fridolin Krausmann (Regional Environmental Change, 2018)

Feeding and cleaning the city: the role of the urban waterscape in provision and disposal in Vienna during the industrial transformation - Sylvia Gierlinger; Gertrud Haidvogl; Simone Gingrich; Fridolin Krausmann (Water History, 2013)

Changes in land use in South Africa between 1961 and 2006: an integrated socio-ecological analysis based on the human appropriation of net primary production framework - Maria Niedertscheider; Simone Gingrich; Karl-Heinz Erb (Regional Environmental Change, 2012)

The Danube and Vienna: urban resource use, transport and land use 1800–1910 - Simone Gingrich; Gertrud Haidvogl; Fridolin Krausmann (Regional Environmental Change, 2012)

The Metabolic Transition in Japan - Fridolin Krausmann; Simone Gingrich; Reza Nourbakhch‐Sabet (Journal of Industrial Ecology, 2011)

Industrialization, Fossil Fuels, and the Transformation of Land Use - Karl‐Heinz Erb; Simone Gingrich; Fridolin Krausmann; Helmut Haberl (Journal of Industrial Ecology, 2008)
Summary Human‐induced changes in global stocks and flows of carbon are major drivers of global climate change. This article presents a comprehensive and systemic account of a nation's carbon budget, comprising socioeconomic as well as ecological carbon flows in a historic time series. The example of Austria 1830–2000, for which excellent databases facilitate a comprehensive assessment, suggests that changes in socioeconomic metabolism during the agrarian−industrial transition are intimately linked with changes in land use and natural carbon flows. In the preindustrial agrarian colonization of Austria (during the thousands of years before 1830), a huge amount of carbon was released due to the expansion of agricultural land. At the dawn of Austria's industrialization (1830–1880), this process was terminated, and carbon inflows and outflows of ecosystems were approximately balanced. With rising fossil fuel consumption, Austria's socioeconomic system added growing amounts of carbon to the atmosphere each year. At the same time, fossil‐fuel‐powered surges in the productivity of agro‐ecosystems facilitated the production of growing amounts of agricultural biomass on shrinking agricultural areas. This greatly enhanced ecological carbon flows and, together with decreasing pressures on forests, allowed ecosystems to recover from past depletion and absorb increasing amounts of carbon. The systematic interlinkage between the socioeconomic energy system and carbon flows in ecosystems, as documented in this study, underlines the need for comprehensive and consistent analyses of society−nature interaction to develop monitoring tools and support strategies aimed at a more sustainable future.

Long-term dynamics of terrestrial carbon stocks in Austria: a comprehensive assessment of the time period from 1830 to 2000 - Simone Gingrich; Karl-Heinz Erb; Fridolin Krausmann; Veronika Gaube; Helmut Haberl (Regional Environmental Change, 2007)